Tax systems in transition - Mitra, Pradeep; Stern, Nicholas (World Bank, Washington, DC, 2014)
How have tax systems, whose primary role is to raise resources to finance public expenditures, evolved in the transition countries of Eastern Europe and the former Soviet Union? The authors find that: (1) the ratio of tax revenue-to-GDP decreased largely due to a fall in revenue from corporate income tax; (2) the fall in revenue from the corporate income tax led to a decline in the importance of income taxes, notwithstanding a rise in the share of individual income tax; (3) social security contributions together with payroll taxes became less important in the Commonwealth of Independent States; and (4) domestic indirect taxes gained in importance in overall tax revenues. Apart from the increased role of personal income taxation, these developments go in a direction opposite to those observed in poor countries as they get richer. They show a key aspect of transition, namely a movement from a system where the government exercised a preeminent claim on output and income before citizens had access to the remainder, to one with a greatly diminished role for the public sector, as reflected in a lower ratio of public expenditure to GDP, where the government needs to collect revenue in order to spend. Can expected levels of public expenditure be financed by the basic instruments of a modern tax system without creating significant distortions in the private sector? The authors suggest that transition countries, depending on their stage of development, should aim for a tax revenue-to-GDP ratio in the range of 22 to 31 percent, comprising value-added tax (6 to 7 percent), excises (2 to 3 percent), income tax (6 to 9 percent), social security contribution together with payroll tax (6 to 10 percent), and other taxes such as on trade and on property (2 percent). The authors' analysis also sheds light on the links between tax policy, tax administration, and the investment climate in transition countries.